Accurate classification of BRCA1 variants with saturation genome editing. (11th October 2018) - Findlay, Gregory; Daza, Riza; Martin, Beth; Zhang, Melissa; Leith, Anh; Gasperini, Molly; Janizek, Joseph; Huang, Xingfan; Starita, Lea; Shendure, Jay
Abstract Variants of uncertain significance fundamentally limit the clinical utility of genetic information. The challenge they pose is epitomized byBRCA1, a tumour suppressor gene in which germline loss-of-function variants predispose women to breast and ovarian cancer. AlthoughBRCA1 has been sequenced in millions of women, the risk associated with most newly observed variants cannot be definitively assigned. Here we use saturation genome editing to assay 96.5% of all possible single-nucleotide variants (SNVs) in 13 exons that encode functionally critical domains of BRCA1. Functional effects for nearly 4, 000 SNVs are bimodally distributed and almost perfectly concordant with established assessments of pathogenicity. Over 400 non-functional missense SNVs are identified, as well as around 300 SNVs that disrupt expression. We predict that these results will be immediately useful for the clinical interpretation ofBRCA1 variants, and that this approach can be extended to overcome the challenge of variants of uncertain significance in additional clinically actionable genes. GermlineBRCA1 loss-of-function variants are associated with predisposition to early-onset breast and ovarian cancer; here the authors use CRISPR/Cas9 genome editing to functionally assess thousands ofBRCA1 variants in order to facilitate the clinical interpretation of these variants.